A novel interplay between GEFs orchestrates Cdc42 activity during cell polarity and cytokinesis in fission yeast - Hercyk, Brian S. (J Cell Sci, 2019)
Cdc42, a conserved regulator of cell polarity, is activated by two GEFs, Gef1 and Scd1, in fission yeast. Why the cell needs two GEFs is unclear, given that they are partially redundant and activate the same GTPase. Using the GEF localization pattern during cytokinesis as a paradigm, we report a novel interplay between Gef1 and Scd1 that spatially modulates Cdc42. We find that Gef1 promotes Scd1 localization to the division site during cytokinesis through recruitment of the scaffold protein Scd2, via a Cdc42 feedforward pathway. Similarly, during interphase Gef1 promotes Scd1 recruitment at the new end to enable the transition from monopolar to bipolar growth. Reciprocally, Scd1 restricts Gef1 localization to prevent ectopic Cdc42 activation during cytokinesis to promote cell separation, and to maintain cell shape during interphase. Our findings reveal an elegant regulatory pattern in which Gef1 primes Cdc42 activation at new sites to initiate Scd1-dependent polarized growth, while Scd1 restricts Gef1 to sites of polarization. We propose that crosstalk between GEFs is a conserved mechanism that orchestrates Cdc42 activation during complex cellular processes. This article has an associated First Person interview with the first author of the paper.